Discontinuous Pulmonary Artery: Utility of Computed Tomographic Angiography and Lung Perfusion Scan in Management. (January 2017) - Eltayeb, Osama; Mongé, Michael C.; Popescu, Andrada R.; Sarwark, Anne E.; Harris, Tyler; Backer, Carl L.
We describe the diagnosis and surgical repair of a five-month-old infant with a congenital discontinuous right pulmonary artery. Initial echocardiogram failed to show the right pulmonary artery and revealed systemic left pulmonary artery pressure based on the tricuspid regurgitation jet. Computed tomographic angiography confirmed the diagnosis of discontinuous right pulmonary artery. The right pulmonary artery appeared essentially normal in size, and there were no significant aortopulmonary collateral arteries. Using cardiopulmonary bypass and aortic transection, we created an anastomosis between the right and the main pulmonary arteries augmented anteriorly by a pericardial patch. Postoperative lung perfusion scan demonstrated balanced pulmonary blood flow to the lungs. Pulmonary hypertension resolved over three weeks in the postoperative period, an expected outcome in this age-group.